2009
DOI: 10.1259/bjr/28896686
|View full text |Cite
|
Sign up to set email alerts
|

MDCT findings of acute aortic dissection with diastolic prolapse of the intimal flap into the left ventricle

Abstract: Acute aortic regurgitation is frequently recognised in patients with Stanford Type A aortic dissection. However, diastolic prolapse of the aortic intimal flap into the left ventricle can cause aortic regurgitation in rare cases. Here is presented an image report of severe aortic regurgitation that was secondary to the back-and-forth intimal flap movement of acute Type A aortic dissection by the use of transthoracic echocardiography and multidetector row CT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…On the rare occasion, massive aortic valve regurgitation can occur owing to a circumferential intimal disruption and prolapse of the cylinder-shaped intimal flap into the left ventricle. 46 Rarely, flap continuity is not clearly visible on axial scans. In such cases, volume rendering reconstructions may be of value, showing greater sensitivity ( Figure 11).…”
Section: Classic Multidetector Ct Findings Of Aortic Dissectionmentioning
confidence: 99%
“…On the rare occasion, massive aortic valve regurgitation can occur owing to a circumferential intimal disruption and prolapse of the cylinder-shaped intimal flap into the left ventricle. 46 Rarely, flap continuity is not clearly visible on axial scans. In such cases, volume rendering reconstructions may be of value, showing greater sensitivity ( Figure 11).…”
Section: Classic Multidetector Ct Findings Of Aortic Dissectionmentioning
confidence: 99%
“…Nevertheless, there have been reports that angiography can reveal aortic dissection with an intimal flap prolapsing into LVOT during diastole [ 2 ]. Currently, multidetector row CT and electrocardiography gated CT can produce clear images and allow detection of aortic dissection with circumferential intimal flap prolapsing into LVOT during diastole and differentiate the intimal flap from aortic valve [ 6 , 9 ]. Preoperative TTE is also a convenient and practical tool to determine aortic dissection with proximal intimo-intimal intussusception [ 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Acute aortic regurgitation is a complication that occurs in patients with aortic dissection involving the ascending aorta. Aortic regurgitation may result from three different mechanisms: (1) the dissection may cause progressive aortic root and annular dilatation, which prevents central leaflet coaptation; (2) the dissection may disturb the aortic root geometry in an asymmetric fashion, with consequent prolapse of one leaflet; and (3) diastolic prolapse of the intimal flap into the left ventricle, which sticks to the aortic valve [1]. In this case, the entry was at the proximal site of the ascending aorta and circumferential dissection extended both anterogradely and retrogradely.…”
Section: Discussionmentioning
confidence: 99%
“…2B and Supplementary video 2). These images suggested that the circumferential intimal flap stuck to the aortic valve, resulting in severe aortic regurgitation (Supplementary video 3) [1]. One day after the admission, the patient underwent resuspension of the commissure between NCC and RCC and replacement of ascending aorta with a prosthetic graft.…”
Section: Case Reportmentioning
confidence: 99%
See 1 more Smart Citation